Soil P Availability in Neutral and Alkaline Soils - DEDI NURSYAMSI; D. SETYORINI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
The availability of soil P for plant growth depends on equilibrium reaction between several P forms in the soils, such as soil soluble, labile, non-labile, as well as organic P. The research that aimed to study soil P availability, form, and sorption, as well as soil properties that affect on P availability in neutral and alkaline soils was conducted in Soil Testing Laboratory, Indonesian Soil Research Institute using 91 topsoil samples (0-20 cm) which have pH neutral-alkaline taken from Java. The samplesconsisted of Inceptisols (13 samples), Vertisols (47 samples), and Alfisols (31 samples). Soil properties analyzed were soil pH H2O (1:5), clay content (pipette), organic-C (Kjeldahl), exch. Ca and Mg (NH4OAc 1 N pH=7), exch. Al (KCl 1 N), and P (HCl 25%, Olsen, and Bray I). Soil P fractionation and sorption were determined using Kuo (1996) and Fox and Kamprath (1970) procedures respectively. The result showed that according to HCl 25%, Olsen, and Bray I extractions, the availability of soil P among the soils was in order of Inceptisols > Vertisols > Alfisols. Whereas the soil P forms in tested soils was in order of residual-P > Ca-P > (Fe+Al)-P > organic-P. Buffering capacity, maximum sorption, as well as bonding energy constant of soil P was in order of Inceptisols > Vertisols > Alfisols. Furthermore, soil properties that effected significantly on the variables of soil P availability were soil clay content, organic-C, and exch. Mg in Inceptisols; clay content and organic-C in Vertisols; as well aspH, clay content, and exch. Ca in Alfisols.